Faktor – Faktor yang Mempengaruhi Ketidakberhasilan ASI Eksklusif pada Ibu Menyusui - Prihatini, Frila Juniar; Achyar, Khamidah; Kusuma, Inggar Ratna (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The failure of exclusive breastfeeding is a common occurrence in Indonesia, despite the government's recommendation for exclusive breastfeeding. This study aims to identify the risk factors for the failure of exclusive breastfeeding. This research utilized a literature review or literature study using a descriptive method. The literature search was conducted through publications in two databases, PubMed and Google Scholar. A strategic search method was employed to obtain journals using the keywords